ASUHAN KEPERAWATAN Ny. M DENGAN PEMBERIAN TERAPI PIJAT WOOLWICH UNTUK MENGATASI MASALAH MENYUSUI TIDAK EFEKTIF - Nella Hetty Sinaga; Didi Yunaspi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
The postpartum period is a critical phase for maternal recovery and the success of breastfeeding. One of the common challenges encountered during this time is ineffective breastfeeding, which can hinder the provision of exclusive breast milk. Woolwich massage therapy is a non-pharmacological intervention aimed at stimulating prolactin and oxytocin hormones, enhancing breast milk production, and improving latch and maternal comfort during breastfeeding. This study employed a case study approach involving Mrs. M, a postpartum mother experiencing ineffective breastfeeding in the working area of Batu Aji Public Health Center. Comprehensive nursing care was provided over three consecutive days, encompassing assessment, diagnosis, intervention, implementation, and evaluation. The primary intervention consisted of administering Woolwich massage therapy for 10–15 minutes daily, accompanied by breastfeeding education and psychological support. After three days of intervention, there was a notable increase in breast milk production, reduction in breast engorgement, and improvement in breastfeeding technique. The client demonstrated enhanced self-confidence, greater comfort during breastfeeding, and the ability to perform independent breast care. These findings align with previous studies indicating that Woolwich massage therapy is effective in addressing ineffective breastfeeding among postpartum mothers. This intervention can be integrated into maternal Keywords: Postpartum, Exclusive Breastfeeding, Woolwich Massage Therapy